Delegation of workload from musculoskeletal physiotherapists to physiotherapy assistants/support workers: A UK online survey. (December 2022) - Sarigiovannis, P.; Foster, N.E.; Jowett, S.; Saunders, B.
Abstract: Purpose: There are approximately 9000 physiotherapy assistants/support workers in the UK. Many of them work in NHS physiotherapy outpatient services treating patients with musculoskeletal conditions, but their role(s) are relatively undefined and as such there is considerable variation in the duties and tasks they undertake. This study aimed to explore current practice of UK musculoskeletal physiotherapists in relation to delegation to physiotherapy assistants/support workers. Methods: An online cross-sectional descriptive survey was designed and collected data on delegation practice and training in delegation. The survey was piloted with 10 physiotherapists. The final questionnaire was distributed via the interactive Chartered Society of Physiotherapy's website and the authors' professional networks via Twitter. Responses were collected over a five-week-period from October to November 2020. Results: Of 302 survey responses, 232 were analysed (46 incomplete, 24 ineligible). The majority of respondents (66.3%, 154/232) had worked as physiotherapists for over 10 years. Most respondents indicated they had neither formal training (84%, 195/232) nor informal training (60.3%, 140/232) regarding how to delegate tasks. The clinical tasks most commonly delegated by physiotherapists were supervision of exercises (81.0%, 188/232) and walking aid provision (78.5%, 182/232) whereas the least delegated clinical task was the application of electrotherapy (19.8%, 46/232). Conclusion: These survey results provide evidence for the need to improve training in delegation for both physiotherapists and physiotherapy assistants, and to ensure clearer delegation processes to facilitate good delegation practice in the musculoskeletal setting.